A Cooperative-Based Community Empowerment Model for Addressing Poverty in Surabaya - Moch. Rafly Dwi Darmawan; Dewien Nabielah Agustin (Universitas Muhammadiyah Jakarta, 2025)
This study aims to examine a cooperative-based community empowerment model as a strategy for addressing poverty in Surabaya. Employing a descriptive qualitative approach, the research explores how cooperatives can function as both economic and social institutions that empower impoverished communities through capacity building, access to capital, and the development of partnership networks. The findings reveal that the cooperative empowerment model is effective in improving members’ welfare, despite several challenges, including limited managerial capacity and uneven member participation. The study recommends strengthening the institutional capacity of cooperatives, enhancing community participation, and providing policy support and digital technology to ensure the sustainability of this empowerment model. This model is expected to serve as a sustainable solution for poverty reduction in Surabaya.